SUSTAINABLE CORROSION INHIBITION OF COPPER USING SANTOL (SANDORICUM KOETJAPE) FRUIT PEEL EXTRACT IN ACIDIC MEDIUM - Ainunsyah, Zul; Gapsari , Femiana; Darmadi, Djarot B.; Sasmito, Muhammad (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Corrosion control is crucial to material protection, particularly in industrial applications where metal degradation leads to significant economic losses. One of the major challenges in corrosion research is finding effective and eco-friendly inhibitors that can replace traditional toxic chemical inhibitors. This study explores the use of Santol (Sandoricum koetjape) fruit peel extract as a potential green inhibitor for copper corrosion in a 1 M HNO3 solution. Electrochemical techniques, including potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS), were used to evaluate the inhibition efficiency of the extract. The results showed a significant reduction in the corrosion rate, with an inhibition efficiency of 77.33% from PDP analysis and 97.50% from EIS measurements. The corrosion current density decreased from 1408.30 microA to 319.25 microA, and the charge transfer resistance increased from 22.56 Ohm to 902.88 Ohm. Santol fruit peel extract effectively inhibits copper corrosion, promoting the development of sustainable corrosion inhibitors and using agricultural waste as an alternative to conventional chemical inhibitors.